Gain‐scheduled constrained state feedback control of DC–DC buck power converter. Issue 4 (1st April 2018) - Tarczewski, Tomasz; Niewiara, Łukasz J.; Skiwski, Michał; Grzesiak, Lech M.
Abstract : A gain‐scheduled constrained state feedback controller (SFC) for a SiC MOSFET direct current (DC)–DC buck power converter with a non‐synchronous control strategy is presented. First, the synthesis process of a gain‐scheduled SFC for a control system with a state‐dependent parameter is proposed. Next, constraints of important states and control variables are a posteriori introduced into control algorithm to provide satisfactory dynamic behaviour and safe operation of the plant. The boundary values of control signals which provide permissible values of the future state‐space variables are derived from the models of power converters that take into account two modes of operation (i.e. charging and discharging mode). The novelty of the proposed approach lies in efficient control algorithm that utilises the gain‐scheduled SFC with the parameter‐dependent constraint handling method. The designed control algorithm is extensively tested through simulation and experiments at a switching frequency of 36 kHz. The proposed solution is further compared with a conventional cascade control structure based on two proportional integral controllers for voltage and current loops as well as with a non‐constrained state feedback control structure to illustrate its performance and low computational complexity.